TELEPON SELULER DAN PERGAULAN BEBAS REMAJA DI KABUPATEN MAMASA SULAWESI BARAT - A.Nur Aisyah Rusnali (Al-Din: Jurnal Dakwah dan Sosial Keagamaan, 2018)
Information Technology, especially mobile telephone, has to develop its technology to cope with the need of the consumers. The purpose of this study to determine how cell phone use among teens from the point of view of teenage promiscuity and criminality in Mamasa, West Sulawesi. The method used is descriptive method with qualitative approach through direct observation of the object of research and interviews with informants related cases of promiscuity and criminality. Then analyzed using interactive model of Miles and Huberman. The results showed that the lack of control and the closeness to the elderly, causing teen cell phone users Mamasa addiction to technology. Teens using cell phones as a medium of communication to build closeness with others and a close friend. juvenile-related cases and crime free peregaulan manggunakan mobile phone without supervision and guidance of parents.Keywordscellular phone; promisquity